PENGARUH PROMOTIONAL MIX DAN WORD OF MOUTH TERHADAP KEPUTUSAN NASABAH DALAM MEMBELI PRODUK JASA ASURANSI JIWA PT PAROLAMAS PADANG - Julita Fetri, Sonya; Dewita Hia, Yulna; Natassia, Rizky (Pendidikan Ekonomi, 2014)
ABSTRACT This study aims to reveal how the promotional mix to influence the customers decision to purchase insurance products and how the influence of word of mouth on customers decision to purchase insurance products Parolamas. The object of research is the customer service life insurance Parolamas Padang. The study population were all customers of life insurance services Parolamas Champaign in 2012 with a sample of 100 customers. The sampling technique used was cluster random sampling. The data analysis technique used is multiple linear regression, based on the results of multiple linear regression equations are as follows : Y = 0.432 + 0.349 + 0.549+0.213. Based on the results of statistical tests, using the t test showed that the promotional mix variable has a significance value 0.000 < 0.05 and word of mouth has a significance value 0.000 < 0.05 so that these variables have a significant influence on the customers decision to purchase insurance products Parolamas soul . Based on the calculation of F count, are jointly independent variable is the promotional mix and word of mouth has a significant level of 0.000 < 0.05, this proves that these variables significantly influence the customers decision to purchase life insurance products Parolamas. Based on the test results of the calculation of the coefficient of determination ( R Square ) indicates that the customers decision to purchase insurance products Parolamas promotional mix variables are influenced by word of mouth and by 73.4 %, while the remaining percentage of 26.6 % is explained by other variables or causes beyond regression models of this study. ABSTRACT This study aims to reveal how the promotional mix to influence the customers decision to purchase insurance products and how the influence of word of mouth on customers decision to purchase insurance products Parolamas. The object of research is the customer service life insurance Parolamas Padang. The study population were all customers of life insurance services Parolamas Champaign in 2012 with a sample of 100 customers. The sampling technique used was cluster random sampling. The data analysis technique used is multiple linear regression, based on the results of multiple linear regression equations are as follows : Y = 0.432 + 0.349 + 0.549+0.213. Based on the results of statistical tests, using the t test showed that the promotional mix variable has a significance value 0.000 < 0.05 and word of mouth has a significance value 0.000 < 0.05 so that these variables have a significant influence on the customers decision to purchase insurance products Parolamas soul . Based on the calculation of F count, are jointly independent variable is the promotional mix and word of mouth has a significant level of 0.000 < 0.05, this proves that these variables significantly influence the customers decision to purchase life insurance products Parolamas. Based on the test results of the calculation of the coefficient of determination ( R Square ) indicates that the customers decision to purchase insurance products Parolamas promotional mix variables are influenced by word of mouth and by 73.4 %, while the remaining percentage of 26.6 % is explained by other variables or causes beyond regression models of this study.